Outcomes of cataract surgery in diabetic patients : Results of the pan american collaborative retina study group (2014)
Purpose: This study was designed to evaluate the visual and anatomical outcomes after cataract surgery in diabetic patients with different intraoperative therapeutic strategies. Methods: The research design comprised of a multicentric, retrospective, interventional study conducted at 6 centers in Argentina, Brazil, Costa Rica, Puerto Rico, Spain, and Venezuela. We included 138 diabetic patients with at least 6-month follow-up following phacoemulsification and intraocular lens implantation. Best-corrected visual acuity (BCVA) and central subfield thickness were collected at baseline and at 1-, 2-, 3-, and 6-month follow-up. Of these, 42 cases were not treated with any intraoperative coadjuvant medication (Group 1), 59 patients received intraoperative bevacizumab (Group 2) and 37 patients received intraoperative triamcinolone (4 mg/0.1 ml) (Group 3). Results: The mean logMAR [± standard deviation (SD)] BCVA improved from 0.82 (± 0.43) at baseline, to 0.14 (± 0.23) at 6-month follow-up (p<0.001) in Group 1; from 0.80 (± 0.48) to 0.54 (± 0.45) (p<0.001) in Group 2; and from 1.0 (± 0.40) to 0.46 (± 0.34) (p<0.001) in Group 3. The mean central subfield thickness increased from 263.57 μm (± 35.7) at baseline to 274.57 μm (± 48.7) at 6-month follow-up (p=0.088) in Group 1; from 316.02 μm (± 100.4) to 339.56 μm (± 145.3) (p=0.184) in Group 2; and from 259.18 μm (± 97.9) to 282.21 μm (± 87.24) (p=0.044) in Group 3. Conclusions: Diabetic patients may significantly benefit from cataract surgery. This study provides evidence to support the use of intravitreal triamcinolone or bevacizumab at the time of cataract surgery in cases with pre-existent diabetic macular edema or moderate-severe non-proliferative diabetic retinopathy.